Spirit of an American Cult: American Civil Religion and the Stories and Imagery Used to Shape American Identity - Law, Colin (Université d'Ottawa / University of Ottawa, 2023)
This thesis explores the use of language, myth creation, and the development of American civil religion to construct a national identity. It analyzes the role of religious language in imagining an identity for the American people, with Protestant Christianity being a driving force for this rhetoric. Throughout this thesis, I argue that specific historical figures have become symbols of American identity, creating an American cult that venerates these figures as sacred icons. This thesis traces the historical development of thought as it relates to American political figures taking on mythical and legendary status in the minds of the citizens. The role of monuments and memorials in Washington, D.C., as capsules into the past and symbolic representations of what is essential to the American people, is also explored. I argue that monuments and memorials have artistic perspectives and use specific imagery that shows how the designers want their audience to view and interpret the events and people who are the subject of the piece and how notions of national identity are projected onto monuments, memorials, and symbols. The thesis also examines the growing phenomenon of far-right nationalism in the United States and how President Trump used populism and rhetoric of American civil religion to strengthen his support. I also explore the variations of patriotic participation through protests by Colin Kaepernick and the Black Lives Matter Movement showing the diverse nature of national identity and civic contribution. The thesis also delves into the importance of the military in the United States and how soldiers have become a symbol of American patriotism and identity. By highlighting the role of religion, language, and mythology in shaping national identity, this thesis sheds light on the complex interplay between culture, history, and identity in the United States.
Keywords: religion; history; civil religion; United States of America; American civil religion; material religion; U.S. military; Washington, D.C.; memorials; monuments; Arlington national cemetery; American legends